We are searching data for your request:

**Forums and discussions:**

**Manuals and reference books:**

**Data from registers:**

**Wait the end of the search in all databases.**

Upon completion, a link will appear to access the found materials.

Upon completion, a link will appear to access the found materials.

We start with the following equality:

-24 = -24

We wrote the number -24 in two different ways:

16 - 40 = 36 - 60

The numbers 16, 40, 36 and 60 can be written as follows:

4x4 - 2x4x5 = 6x6 - 2x6x5

We can add 25 on both sides of the equation without changing it:

4x4 - 2x4x5 + 5x5 = 6x6 - 2x6x5 + 5x5

Now we see that on both the left and right sides we have a squared binomial (the first squared term minus twice the product of the two terms plus the second squared)

(4 - 5)^{2} = (6 - 5)^{2}

Eliminating the square on both sides of the equation gives us:

4 - 5 = 6 - 5

Finally, by adding 5 on both sides, we get the result:

4 = 6

Obviously this demonstration has an error because we all know that 4 is not equal to 6 (or does anyone have any questions?). Click below to find out what the error is:

In this demonstration comes a stage where we have:

**(4-5) ^{2} = (6-5)^{2}**

According to the demonstration, the next step is:

Take the square root on both sides, obtaining:

**4-5 = 6-5**

**There is the mistake !!!**

It is wrong because **SQUARE ROOT** of a number **SQUARED** is equal to **MODULE** of this number. So the correct would be:

**| 4-5 | = | 6-5 |**

**| -1| = | 1 |**

**1 = 1**